2011
DOI: 10.1186/1755-8166-4-23
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of sex chromosome abnormalities in a cohort of 95 Indonesian patients with monosomy X

Abstract: BackgroundMonosomy × or 45,X is a cytogenetic characteristic for Turner syndrome. This chromosome anomaly is encountered in around 50% of cases, but wide variations of other anomalies have been found. This report is to describe the cytogenetic characteristics of 45,X individuals. To the best of our knowledge, there were no large series of 45,X cases has been reported from Indonesia.ResultsNinety five cases with 45,X cell line found, of which 60 were detected by karyotyping, 4 by FISH for sex chromosomes, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
7
0
3
Order By: Relevance
“…While patients with mosaicism for 46,XY cell line or structural rearrangement of the Y chromosome mostly have masculinized external genitalia and are at increased risk for having gonadoblastoma and other gonadal tumor. 12,20,21 Thus, early intervention should be done for orchidectomy. 22 In this study we observed 1 patient with marker chromosome 45,X(98%)/46,X mar(2%) with clinical profile of this patient showed short stature and no other dysmorphic features, compared to the previous study which reported severe phenotype manifestations in those type of Turner variants, 16 this could be due to the low percentage of marker X.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While patients with mosaicism for 46,XY cell line or structural rearrangement of the Y chromosome mostly have masculinized external genitalia and are at increased risk for having gonadoblastoma and other gonadal tumor. 12,20,21 Thus, early intervention should be done for orchidectomy. 22 In this study we observed 1 patient with marker chromosome 45,X(98%)/46,X mar(2%) with clinical profile of this patient showed short stature and no other dysmorphic features, compared to the previous study which reported severe phenotype manifestations in those type of Turner variants, 16 this could be due to the low percentage of marker X.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, conventional cytogenetic method can missed the Y component up to 9.3%. 21 Detection of Y chromosome complement and their composition is important in genetic counseling, because of the association with the risk of gonadoplastoma. 9,12,20 In this study the most common cause of primary amenorrhea was gonadal dysgenesis Turner Syndrome followed by MRKH, pure gonadal dysgenesis, CAH, CAIS and PAIS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar reasoning could be used in case 3, where the male patient, although carrying a duplicated Y fragment, presented with ambiguous genitalia and undescended testes. Y chromosome aberrations, especially of the isodicentric type are known to be very unstable during cell division, generating alternating cell lines [Marzuki et al, 2011]. Lungeanu et al [2008] suggested that in these isodicentric aberrations initially both centromeres of the Y chromosome were completely functional and that the loss of this chromosome through failure of correct mitotic segregation and anaphase produced increasing amounts of 45,X cells, thus leading to TS.…”
Section: Discussionmentioning
confidence: 99%
“…Sendroma neden olan karyotipik anomaliler içerisindeensıkmonozomiX(45,X)görülürken,bunu mozaikkaryotipler(45,X/46,XX,45,X/47,XXXvs)ve Xkromozomununyapısalanormallikleri(izokromozom X(i(X)),ringX(r(X))takipeder (1,(3)(4)(5).…”
Section: Introductionunclassified